2016
DOI: 10.1080/19404476.2016.1138727
|View full text |Cite
|
Sign up to set email alerts
|

A Phenomenological Study of Middle Grade Female and Male Students’ Single-Sex Mathematical Experiences

Abstract: Utilizing a descriptive phenomenological design, this study examines the lived experiences of seven middle grade students, four females and three males, enrolled in a single-sex mathematics classroom within a coeducational school setting. The intent of the study is to understand, from students themselves, about the experience of single-sex mathematics classrooms in public schools. The findings reveal that, as a whole, participants do not foreground their experience within the academic discipline under study (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
1
1
Order By: Relevance
“…Whereas some studies have shown that girls reported better perceptions of self‐concept, or positive social experiences within the mathematics classrooms (e.g., Hughes et al, ; Simpson & Che, ), results from this study do not indicate, for girls at least, that participation in single‐sex classes results in a greater propensity to stereotype mathematics as a gendered domain than would be the case in coeducational classes. The results do not suggest that simply being in a classroom with one's own gender, in this case female peers, leads to explicit in‐group bias as girls in single‐sex and coeducational classrooms in this study seem to perceive mathematics as a neutral and more female oriented domain.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Whereas some studies have shown that girls reported better perceptions of self‐concept, or positive social experiences within the mathematics classrooms (e.g., Hughes et al, ; Simpson & Che, ), results from this study do not indicate, for girls at least, that participation in single‐sex classes results in a greater propensity to stereotype mathematics as a gendered domain than would be the case in coeducational classes. The results do not suggest that simply being in a classroom with one's own gender, in this case female peers, leads to explicit in‐group bias as girls in single‐sex and coeducational classrooms in this study seem to perceive mathematics as a neutral and more female oriented domain.…”
Section: Discussioncontrasting
confidence: 99%
“…Single‐sex classes in coeducational schools generally seem to benefit girls more than boys (e.g., Glasser, ). More specifically, girls enrolled in single‐sex settings are purported to make considerable gains in achievement in mathematics (Baker, ); feel empowered to voice their ideas and opinions as the class is viewed as an open and liberal environment (Hughes, Nzekwe, & Molyneaux, ; Simpson & Che, ); and report higher perceptions of self as a learner of mathematics (Baker, ) as compared to girls enrolled in coeducational classes.…”
Section: Literature Reviewmentioning
confidence: 99%